2019
DOI: 10.1073/pnas.1820297116
|View full text |Cite
|
Sign up to set email alerts
|

Increased Muscleblind levels by chloroquine treatment improve myotonic dystrophy type 1 phenotypes in in vitro and in vivo models

Abstract: Myotonic dystrophy type 1 (DM1) is a life-threatening and chronically debilitating neuromuscular disease caused by the expansion of a CTG trinucleotide repeat in the 3′ UTR of the DMPK gene. The mutant RNA forms insoluble structures capable of sequestering RNA binding proteins of the Muscleblind-like (MBNL) family, which ultimately leads to phenotypes. In this work, we demonstrate that treatment with the antiautophagic drug chloroquine was sufficient to up-regulate MBNL1 and 2 proteins in Drosophila and mouse … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(52 citation statements)
references
References 53 publications
1
51
0
Order By: Relevance
“…An antisense oligonucleotide-based reagent, ISIS-DMPK-2.5 RX , was the first potential DM1-specific drug which underwent clinical research [ 304 , 310 ]. However, due to low therapeutic effect in DM1 patients’ tissues the trial was halted whereas new potential reagents are being intensively screened [ 309 , 311 , 312 , 313 ].…”
Section: Splicing-related Diseases Mediated By Rna Structural Arramentioning
confidence: 99%
“…An antisense oligonucleotide-based reagent, ISIS-DMPK-2.5 RX , was the first potential DM1-specific drug which underwent clinical research [ 304 , 310 ]. However, due to low therapeutic effect in DM1 patients’ tissues the trial was halted whereas new potential reagents are being intensively screened [ 309 , 311 , 312 , 313 ].…”
Section: Splicing-related Diseases Mediated By Rna Structural Arramentioning
confidence: 99%
“…However, at the 40-mg/kg dose, the transcribed levels of Mbnl1 in mouse muscle exceeded 2 to 2.5 times the level of endogenous expression in FVB mice, according to the levels observed in other experiments where the level of expression of Mbnl1 mRNA between HSA LR mice treated with PBS and FVB is similar. 28 Likewise, the 12.5-mg/kg dosage also shows a healthy rescue of Mbnl1 protein levels and distribution, mis-splicing, myotonia, and muscle weakness. These results emphasize that antagomiR-23b can be fine-tuned to an effective and nontoxic concentration.…”
Section: Discussionmentioning
confidence: 94%
“… 24 , 25 , 26 Muscleblind overexpression also rescued muscle atrophy and excessive autophagy levels in an inducible fly model, 27 and autophagy was reduced after treatment with Muscleblind-increasing chloroquine treatment in the same model. 28 MBNL1 upregulation in DM1 mice and patient-derived fibroblasts is well tolerated and rescues several symptoms, such as myotonia and mis-splicing events, as well as the reduction of foci formation. 29 , 30 , 31 Finally, genetic variations in the promoter of MBNL1 have been shown to correlate with disease severity, further implicating MBNL1 in DM1.…”
Section: Introductionmentioning
confidence: 94%
“…Several candidate therapies have been tested in DM1 models, but none have reached clinical practice yet. Bargiela et al suggested chloroquine as a possible strategy based on the finding that chloroquine treatment is able to upregulate musclebind levels in in vitro and in vivo models [17]. At the beginning of the COVID-19 pandemic, (hydroxy)chloroquine was proposed as one of the most promising drugs due to its anti-viral and immunosuppressive properties.…”
Section: Discussionmentioning
confidence: 99%